Willingness to accept COVID-19 vaccine and its determinants in Ethiopia: A systematic review and meta-analysis - Tolossa, Tadesse; Fetensa, Getahun; Feyisa, Bikila Regassa; Wakuma, Bizuneh; Lema, Matiyos (Frontiers in Virology, 2023)
Introduction: Vaccination is one of the most crucial strategies in the control of pandemics such as COVID-19. Although a couple of research has been conducted to assess the willingness of the population to accept the COVID-19 vaccine, the findings are inconsistent and inconclusive. This study aimed to assess the pooled willingness to uptake the COVID-19 vaccine and its determinants in Ethiopia. Methods: Published and unpublished articles were accessed from various electronic databases and digital libraries. A random-effects model was used to estimate the pooled effect size with a 95% confidence interval. Inverse variance (I2) was used to visualize the presence of heterogeneity. Publication bias was assessed using funnel plots and Egger’s statistical test. Results: A total of 2345 studies were identified from several databases and 16 studies fulfilled the eligibility criteria and were included in the final meta-analysis. The pooled magnitude of willingness to accept the COVID-19 vaccine in Ethiopia was 55.19 % (95% CI: 42.91, 67.48). The current meta-analysis indicated that age greater than 25 years (OR=1.49, 95% CI: 1.12, 1.98) and having a good attitude towards the COVID-19 vaccine (3.57, 95% CI: 1.46, 8.72) were significantly associated with the COVID-19 vaccine uptake. Conclusions and Recommendations: In general, the magnitude of the COVID-19 vaccine acceptance rate among the public is unacceptably low in Ethiopia. Therefore, there is a need to build public trust through the provision of reliable and consistent information about vaccines using different media outlets. Key words: COVID-19 vaccine, COVID-19 vaccine uptake, willingness to accept COVID-19 vaccine, Vaccine acceptance, Ethiopia